Furanocoumarins from Ruta chalepensis with Amebicide Activity - Bazaldúa Rodríguez, Aldo Fabio; Quintanilla Licea, Ramiro; Verde Star, María Julia; Hernández García, Magda Elizabeth; Vargas Villarreal, Javier; Garza González, Jesús Norberto (Molecular Diversity Preservation International, 2021)
Entamoeba histolytica (protozoan; family Endomoebidae) is the cause of amoebiasis, a disease related to high morbidity and mortality. Nowadays, this illness is considered a significant public health issue in developing countries. In addition, parasite resistance to conventional medicinal treatment has increased in recent years. Traditional medicine around the world represents a valuable source of alternative treatment for many parasite diseases. In a previous paper, we communicated about the antiprotozoal activity in vitro of the methanolic (MeOH) extract of Ruta chalepensis (Rutaceae) against E. histolytica. The plant is extensively employed in Mexican traditional medicine. The following workup of the MeOH extract of R. chalepensis afforded the furocoumarins rutamarin (1) and chalepin (2), which showed high antiprotozoal activity on Entamoeba histolytica trophozoites employing in vitro tests (IC50 values of 6.52 and 28.95 µg/mL, respectively). Therefore, we offer a full scientific report about the bioguided isolation and the amebicide activity of chalepin and rutamarin.